Estuary planning and management in Portugal: sharing local boundaries for water resources management - Fidélis, Teresa (2013)
Estuaries concentrate complex and often conflicting sets of natural, economic and social resources and activities bringing multiple challenges to institutional frameworks, planning and management approaches as well as governance practices dedicated to their protection, maintenance and resilience. Portugal has recently adopted a new set of estuary plans of regulatory nature, which combine the perspective of water resources management with that of land-use management. This paper explores the conceptual specificities of estuary planning and management in Portugal and their potential role in contexts of multiple resources, users, instruments and institutions. Given the mentioned complexity and vulnerability to global change, these plans may be crucial for seeking better environmental governance and greater resilience. The paper is structured in three parts. The first one through a literature review summarises some of the main conclusions about the role and specificities of governance in estuaries. The second part presents the legal and procedural features of estuary plans in Portugal and their integration within the water resources and land-use planning systems. The third part concentrates on the specificities of the River Vouga Estuary (Ria de Aveiro), a Natura 2000 area that needs to deal with different, and potentially conflicting, socioeconomic sectors. Departing from a SWOT analysis of the main environmental, socioeconomic and institutional features, the paper argues for the relevance of an innovative planning and management instrument — capable of reducing the tensions inherent to local administrative boundaries and of contributing to a collective vision of the territory through the articulation of values, targets, instruments and means.